The impact of oxidative stress-induced mitochondrial dysfunction on diabetic microvascular complications - Zhang, Ziwei; Huang, Qingxia; Zhao, Daqing; Lian, Fengmei; Li, Xiangyan; Qi, Wenxiu (Frontiers in Endocrinology, 2023)
Abstract：Diabetes mellitus (DM) is a metabolic disease characterised by chronic hyperglycaemia, with absolute insulin deficiency or insulin resistance as the main cause, and causes damage to various target organs including the heart, kidney and neurovascular. In terms of the pathological and physiological mechanisms of DM, oxidative stress is one of the main mechanisms leading to DM and is an important link between DM and its complications. Oxidative stress is a pathological phenomenon resulting from an imbalance between the production of free radicals and the scavenging of antioxidant systems. The main site of reactive oxygen species (ROS) production is the mitochondria, which are also the main organelles damaged. In a chronic high glucose environment, impaired electron transport chain within the mitochondria leads to the production of ROS, prompts increased proton leakage and altered mitochondrial membrane potential (MMP), which in turn releases cytochrome c (cyt-c), leading to apoptosis. This subsequently leads to a vicious cycle of impaired clearance by the body's antioxidant system, impaired transcription and protein synthesis of mitochondrial DNA (mtDNA), which is responsible for encoding mitochondrial proteins, and impaired DNA repair systems, contributing to mitochondrial dysfunction. This paper reviews the dysfunction of mitochondria in the environment of high glucose induced oxidative stress in the DM model, and looks forward to providing a new treatment plan for oxidative stress based on mitochondrial dysfunction.